1996
DOI: 10.1007/bf00184256
|View full text |Cite
|
Sign up to set email alerts
|

Tumorzelldissemination in das Knochenmark und in die Peritonealhohle eine immunzytochemische Untersuchung an Patienten mit einem Magen- oder kolorektalen Karzinom

Abstract: The tumor spread and the radicality of surgical resection are the most important facts in a patient's prognosis. In spite of curative tumor resection many patients die from metastases or local tumor recurrence. One possible reason is early dissemination of tumor cells which cannot be detected with clinical methods of examination. For this reason the aim of our study was to examine both bone marrow and peritoneal lavage for disseminated tumor cells with an immunocytochemical technique in patients with a gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 24 publications
(52 reference statements)
0
12
1
Order By: Relevance
“…Although the true incidence of early lymphatic metastasis in different tumor entities remains finally to be resolved, it has become more and more evident that approximately one third to one half of nodal-negative gastrointestinal cancer patients will exhibit ITCs in locoregional lymph nodes. The relative amount of ITCs in the bone marrow (10%) was rather low in the present report when compared to other audits where it varies broadly between 10 [35] and 82% [36], with a mean value of roughly 20 to 30%. This issue may be related to the different antibodies administered (Ber-EP4 herein vs anticytokeratin antibodies in the literature) and different amount of cells screened.…”
Section: Discussioncontrasting
confidence: 57%
“…Although the true incidence of early lymphatic metastasis in different tumor entities remains finally to be resolved, it has become more and more evident that approximately one third to one half of nodal-negative gastrointestinal cancer patients will exhibit ITCs in locoregional lymph nodes. The relative amount of ITCs in the bone marrow (10%) was rather low in the present report when compared to other audits where it varies broadly between 10 [35] and 82% [36], with a mean value of roughly 20 to 30%. This issue may be related to the different antibodies administered (Ber-EP4 herein vs anticytokeratin antibodies in the literature) and different amount of cells screened.…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies have shown that IDT BM represent a prognostic deterioration of afflicted patients. However, the results are still contradictory as regards lymph glands and there are too few data as regards peritoneal lavage and venous blood [1,2,6,7,12,25]. The goal of our prospective, 6-year on-going study is to compare the rating of IDT BM with established prognosis factors so as to develop recommendations for treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Immunocytochemical analysis, which various research groups have been developing for over 10 years, has also been validated in terms of its clinical relevance [1,2,4,12,14,21]. At present, this analysis is regarded as the standard method for detecting occult, early dissemination of solid tumor cells [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…When using immunocytological methods disseminated tumor cells in the peritoneal cavity could be found in 20–72% of patients in a stage-dependent manner [18, 20, 21, 22, 23], the detection of tumor cells was of prognostic relevance in a number of these studies [20, 21, 23]. Schott et al [20]for example could show that the overall 4-year survival was significantly better in patients negative for immunohistochemical detection of disseminated peritoneal tumor cells in comparison to positive patients (p < 0.005).…”
Section: Gastric Cancermentioning
confidence: 99%
“…Studies using cytology and immunocytochemistry for the detection of disseminated cells in the peritoneal cavity of colorectal cancer patients revealed a detection rate between 27 and 74% [20, 21, 22, 33]. Leather et al [33]compared tumor cell detection in peritoneal washes with conventional cytology and immunohistochemistry before and after resection of colorectal cancer: 43% of patients showed tumor cells in their peritoneal cavities, and there was no significant difference in the frequency of tumor cell detection between pre- and post-resection peritoneal lavages.…”
Section: Colorectal Cancermentioning
confidence: 99%